Role of Voluntary Organizations in Promoting House Hold Livelihoods - Deepmala Singh , Prahalad Mishra and D.K. Singh, (Indian Journal of Extension Education, 2016)
Women are the key contributors to house hold economy and to combating poverty through remunerative and nonremunerative activities at home, in community and at working place. The present study was undertaken to assess the roleof Voluntary organizations towards livelihood security of Rural Women. The study was conducted with 200 respondentsrandomly selected in 8 villages of Jabalpur district, results showed that majority of respondent found in low category ofsocial status, medium personal assets, low physical assets, low human assets and low financial assets of livelihoodsecurity. The majority of respondent were low in overall Livelihood assets of livelihood security